2020
DOI: 10.1111/sms.13683
|View full text |Cite
|
Sign up to set email alerts
|

Testing the validity and reliability of the doping willingness in sport scale

Abstract: Although research investigating doping in sport is burgeoning, there is still a lack of proxy measures of doping behavior that have undergone extensive psychometric testing. To address this issue, we modified a previously used measure of doping willingness in sport and tested aspects of validity and reliability across four studies. In Study 1, we provided support for the face and content validity of the items, and then found support for the factor structure of the scale in a sample of athletes (N = 205) using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Doping willingness refers to 'an openness to take a banned substance in certain risk conducive situations or contexts even if there was no prior intention to do so' (Stanger, Whitaker, & Backhouse, 2020). Research utilizing the PWM has found that athletes were most willing to dope for various reasons; (1) continuing compete at their current level; (2) suffering from an injury; (3) experiencing external pressure from coaches and peers; (4) increasing chances for team selection, gaining a contact, or funding, (5); perceiving everyone else is doping; (6) perceiving they are underperforming in practice or competition; (7) being offered by trusted others; and (8) perceiving doping can quickly enhancing physical condition (Stanger et al, 2020;Whitaker et al, 2017). Willing for using androgenic-anabolic steroids was found one of the most important factor in determining the behavioural intention (Manoochehri et al, 2021).…”
Section: Research Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Doping willingness refers to 'an openness to take a banned substance in certain risk conducive situations or contexts even if there was no prior intention to do so' (Stanger, Whitaker, & Backhouse, 2020). Research utilizing the PWM has found that athletes were most willing to dope for various reasons; (1) continuing compete at their current level; (2) suffering from an injury; (3) experiencing external pressure from coaches and peers; (4) increasing chances for team selection, gaining a contact, or funding, (5); perceiving everyone else is doping; (6) perceiving they are underperforming in practice or competition; (7) being offered by trusted others; and (8) perceiving doping can quickly enhancing physical condition (Stanger et al, 2020;Whitaker et al, 2017). Willing for using androgenic-anabolic steroids was found one of the most important factor in determining the behavioural intention (Manoochehri et al, 2021).…”
Section: Research Problemmentioning
confidence: 99%
“…Doping willingness. The 9-item doping willingness in sport scale (Stanger et al, 2020) was used to assess participants' willingness to dope. Participants responded on a 5-point Likert scale, ranging from 1 (not at all willing) to 5 (extremely willing).…”
Section: Socio-demographic Data and Doping Experiencesmentioning
confidence: 99%
“…The methods for assessing explicit attitudes toward doping are based on self-reported measures, which remain the most commonly used measures in prevention programs (e.g., the Performance Enhancement Attitude Scale, Petróczi & Aidman, 2009; the Doping Willingness in Sport Scale, Stanger et al, 2020). Although the TPB successfully contributes to predicting health behaviors (e.g., Hamilton et al, 2020), Sheeran (2005) concluded his review indicating that not more than 25 to 30% of the behavioral variance could be explained by socialcognitive variables from this line of modeling.…”
Section: Introductionmentioning
confidence: 99%
“…The year 2020 has been unprecedented and exceptionally complex, also in the context of anti-doping efforts in situations of considerable restrictions, lockdowns, reduced options for training and competition, and collection and analysis of anti-doping samples. Probably more than ever, understanding an athlete's attitude towards doping, [1][2][3] the susceptibility and motivation(s) to cheat, identifying factors that influence or predict an athlete's (anti-)doping position and behavior, [4][5][6][7][8] and approaches that support strengthening and consolidating highest levels of sportspersonship as well as harm reduction strategies, 9 have been required to effectively limit intentional anti-doping rule violations (ADRVs).…”
Section: Introductionmentioning
confidence: 99%
“…ence or predict an athlete's (anti-)doping position and behavior, [4][5][6][7][8] and approaches that support strengthening and consolidating highest levels of sportspersonship as well as harm reduction strategies, 9 have been required to effectively limit intentional anti-doping rule violations (ADRVs).…”
mentioning
confidence: 99%